2011
DOI: 10.1073/pnas.1101791108
|View full text |Cite
|
Sign up to set email alerts
|

Humanized mice with ectopic artificial liver tissues

Abstract: "Humanized" mice offer a window into aspects of human physiology that are otherwise inaccessible. The best available methods for liver humanization rely on cell transplantation into immunodeficient mice with liver injury but these methods have not gained widespread use due to the duration and variability of hepatocyte repopulation. In light of the significant progress that has been achieved in clinical cell transplantation through tissue engineering, we sought to develop a humanized mouse model based on the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
149
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(150 citation statements)
references
References 43 publications
0
149
0
1
Order By: Relevance
“…The suitability of this model for antiviral drug testing after successful infection of the chimeric liver by hepatitis B and C viruses was demonstrated, legitimating to believe in future successful infection by human Plasmodium species. Also, very recently, researchers at the MIT developed artificial humanised mouse livers engineered by growing human hepatocytes and human liver endothelial cells with mouse fibroblasts in a three-dimensional polymeric scaffold, and implanted them into mice (Chen et al, 2011). The ectopic livers responded to drugs in a way very similar to the way a human liver does.…”
Section: The P Falciparum-human Hepatocyte Mouse Modelsmentioning
confidence: 99%
“…The suitability of this model for antiviral drug testing after successful infection of the chimeric liver by hepatitis B and C viruses was demonstrated, legitimating to believe in future successful infection by human Plasmodium species. Also, very recently, researchers at the MIT developed artificial humanised mouse livers engineered by growing human hepatocytes and human liver endothelial cells with mouse fibroblasts in a three-dimensional polymeric scaffold, and implanted them into mice (Chen et al, 2011). The ectopic livers responded to drugs in a way very similar to the way a human liver does.…”
Section: The P Falciparum-human Hepatocyte Mouse Modelsmentioning
confidence: 99%
“…To address this problem, we (Hasegawa et al, 2011) and others (reviewed in Yoshizato and Tateno, 2009;de Jong et al, 2010) have developed chimeric mice, in which mouse liver is replaced by transplanted human liver cells or tissue-engineered human liver (Chen et al, 2011). In one model system, uroplasminogen activator transgene expression facilitates the growth of transplanted human liver cells (Vyse et al, 1997;Tateno et al, 2004;Meuleman et al, 2005;Azuma et al, 2007;, whereas a fumarylacetoacetate hydrolase knockout mouse is used in the other system (Azuma et al, 2007) (Bissig et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There are multiple examples in which chimeric mice have been shown to produce known human-specific metabolites for several test substrates (Tateno et al, 2004;Chen et al, 2011;Hasegawa et al, 2011), including steroids Lootens et al, 2009;Pozo et al, 2009;Kamimura et al, 2010). However, we do not know whether chimeric mice can be used to predict the pattern of human drug metabolism for a candidate therapeutic before human clinical testing.…”
Section: Introductionmentioning
confidence: 99%
“…Successful engraftment relies on the severe and acute damage in the recipients, the degree of which is unpredictable, difficult to reproduce, and dependent on many variable factors. 3 More importantly, several clinical trials have reported the disappointing clinical outcomes of cell transplantation methods, as well as potential adverse events. 4,5 Given the limitations of cell replacement strategies, tissue engineering holds a number of possibilities for clinical use.…”
Section: Introductionmentioning
confidence: 99%